Passionflower in the treatment of generalized anxiety disorder: a double-blind and randomized trial with oxazepam - Mohsen Vaziran; Azin Khazaeli; Hamidreza Naghavi; Shahin Akhondzadeh (Institue of Medicinal Plants, ACECR, 2002)
Passionflower (Passiflora incarnata) is folk remedy for anxiety. A double-blind randomized trial compared the efficacy of Pascinora incarnata extract with oxazepam in the treatment of generalized anxiety disorder. The study was performed on 36 patients. They were outpatients and had been diagnosed with generalized anxiety disorder (GAD) using DSM-IV criteria. Patients were allocated in a random fashion 18 to Passiflora extract 45 drops/day plus placebo tablet and 18 to oxazepam 30 mg/day plus placebo drops for a 4-weck trial. Passiflore extract and oxazepam were effective in the treatment of generalized anxiety disorder. No significant difference was observed between the two protocols at the end of trial. Oxazepam showed a rapid onset of action. On the other hand, significantly more problems relating to impairment of job performance was encountered with subjects on oxazepam, We concluded that passiflora extract is an effective drug for the management of generalized anxiety disorer and the incidence of impairment of job performance with passiflora extract compared to oxazepam is an advantage.